2001
DOI: 10.1021/ic010510+
|View full text |Cite
|
Sign up to set email alerts
|

Pyrazolylborate−Zinc−Hydrosulfide Complexes and Their Reactions

Abstract: Four new hydrosulfide complexes Tp*Zn-SH of substituted pyrazolylborate ligands (Tp*) were prepared by reactions of Tp*Zn-OH with H(2)S, and three of them were structurally characterized. Unlike the Tp*Zn-OH complexes they do not react with esters, phosphates, or CO(2), e.g. for thiolytic cleavage reactions. They also cannot be deprotonated, as various bases induce precipitation of ZnS and release of anionic Tp*. Acidic organic X-OH compounds (carboxylic acids, trinitrophenol, hexafluoroacetylacetone) replace … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
55
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 39 publications
12
55
0
Order By: Relevance
“…It is worth noting that a similar reaction has not previously been reported in the literature; even the available structural models for the sulfur-analog CA, e.g. Tp Ph,Me ZnSH, [15] do not react with heterocumulenes. In the past, numerous computational studies have examined the fixation of heterocumulenes by zinc hydroxide complexes, but only one addresses zinc hydrosulfides and the mechanism of their heterocumulene reactions.…”
Section: Introductionsupporting
confidence: 59%
“…It is worth noting that a similar reaction has not previously been reported in the literature; even the available structural models for the sulfur-analog CA, e.g. Tp Ph,Me ZnSH, [15] do not react with heterocumulenes. In the past, numerous computational studies have examined the fixation of heterocumulenes by zinc hydroxide complexes, but only one addresses zinc hydrosulfides and the mechanism of their heterocumulene reactions.…”
Section: Introductionsupporting
confidence: 59%
“…[12][13][14][15]26,27] In this case, the methylation (as well as any other reaction) is restricted to occur at the thiolate side of the complex cation. As the coordination of the reacting molecules to Zn II implicates a steric demand, the degree of obstruction of the zinc(II) ion by the macrocycle should have a pivotal influence on the geometry of the transition state.…”
Section: Steric Influencesmentioning
confidence: 99%
“…[26] Quantum mechanical calculations have revealed that a zinc hydrosulfide moiety His 3 Zn-SH is formed in the course of this interconversion. [27] A suitable structural model − the neutral hydrosulfide complex Tp Ph,Me ZnSH − has been found by Vahrenkamp et al [28,29] Our efforts to obtain an equivalent zinc hydrosulfide complex with an azamacrocyclic ligand were not successful because these compounds are not stable. Nevertheless, due to their positive overall charge, our thiolate complexes also could be regarded as suitable model systems for this species.…”
Section: Introductionmentioning
confidence: 99%